1998
DOI: 10.1021/es9708326
|View full text |Cite
|
Sign up to set email alerts
|

Estimate of Net Trophic Transfer Efficiency of PCBs to Lake Michigan Lake Trout from Their Prey

Abstract: Most of the polychlorinated biphenyl (PCB) body burden accumulated by lake trout (Salvelinus namaycush) from the Laurentian Great Lakes is from their food. We used diet information, PCB determinations in both lake trout and their prey, and bioenergetics modeling to estimate the ef ficiency with which Lake Michigan lake trout retain PCBs from their food. Our estimates were the most reliable estimates to date because (a) the lake trout and prey fish sampled during our study were all from the same vicinity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…He also tried to estimate how this model would work in the field and concluded that at a log K OW value of greater than six, subsequent increases in K OW would not result in proportional increases in the bioconcentration factor because of the effects of transfer efficiency and growth in the study animals (compare, e.g., [32]). Later, a model for net trophic transfer of PCBs was developed for piscivorous fish that corrected for growth effects in the predator [33], and this model was further improved by taking predator age into account [34]. In the current study, PCBs with a range of K OW values that gives maximum uptake efficiency and a nonlinear increase after a K OW value of greater than six are included, which may explain why most PCB congeners had approximately the same BMF (both in salmon and in parasites).…”
Section: Discussionmentioning
confidence: 99%
“…He also tried to estimate how this model would work in the field and concluded that at a log K OW value of greater than six, subsequent increases in K OW would not result in proportional increases in the bioconcentration factor because of the effects of transfer efficiency and growth in the study animals (compare, e.g., [32]). Later, a model for net trophic transfer of PCBs was developed for piscivorous fish that corrected for growth effects in the predator [33], and this model was further improved by taking predator age into account [34]. In the current study, PCBs with a range of K OW values that gives maximum uptake efficiency and a nonlinear increase after a K OW value of greater than six are included, which may explain why most PCB congeners had approximately the same BMF (both in salmon and in parasites).…”
Section: Discussionmentioning
confidence: 99%
“…Long‐term elimination of PCBs via excretion in fish occurs at such a low rate that this rate is practically undetectable (Weininger 1978; Madenjian et al. 1998c), and therefore, long‐term elimination would not be expected to influence the ratio of male PCB concentration to female PCB concentration.…”
Section: Potential For Sex Differences In Gge To Explain Sex Differenmentioning
confidence: 99%
“…Bioenergetics models have been developed and evaluated in attempts to understand implications of changes in prey densities and pollutant burdens on chemical accumulation in species including chinook (Oncorhynchus tshawytscha) and coho salmon (Oncorhynchus kisutch) and lake trout (Jackson and Schindler 1996;Madenjian et al 1998aMadenjian et al , 1998b. These studies have primarily focused on pollutant food web transfer efficiencies rather than the importance of bioenergetic processes in regulating observed spatial and temporal trends.…”
Section: Introductionmentioning
confidence: 99%